Portal-mesenteric vein resection for pancreatic cancer: Results in par with the defined benchmark outcomes - Tsiotos, Gregory G.; Ballian, Nikiforos; Milas, Fotios; Ziogou, Panoraia; Papaioannou, Dimitrios; Salla, Charitini; Athanasiadis, Ilias; Stavridi, Flora; Strimpakos, Alexios; Psomas, Maria; Kostopanagiotou, Georgia (Frontiers in Surgery, 2023)
Background Patients with pancreatic cancer (PC), which may involve major peripancreatic vessels, have been generally excluded from surgery, as resection was deemed futile. The purpose of this study was to analyze the results of portomesenteric vein resection in borderline resectable or locally advanced PC. This study comprises the largest series of such patients in Greece. Materials and Methods Investigator-initiated, retrospective, noncomparative study of patients with borderline resectable or locally advanced adenocarcinoma undergoing pancreatectomy en-block with portal and/or superior mesenteric vein resection in a tertiary referral center in Greece between January 2014 and October 2021. Follow-up was complete up to December 2021. Operative and outcome measures were determined. Results Forty patients were included. Neoadjuvant therapy was administered to only 58% and was associated with smaller tumor size (median: 2.9 cm vs. 4.2 cm, p = 0.004), but not with increased survival. Though venous wall infiltration was present in 55%, it was not associated with tumor size, or Eastern Cooperative Oncology Group (ECOG) status. Resection was extensive: a median of 27 LNs were retrieved, R0 resection rate (≥1 mm) was 87%, and median length of resected vein segments was 3 cm, requiring interposition grafts in 40% (polytetrafluoroethylene). Median ICU stay was 0 days and length of hospitalization 9 days. Postoperative mortality was 2.5%. Median follow-up was 46 months and median overall survival (OS) was 24 months. Two-, 3- and 5-year OS rates were 49%, 33%, and 22% respectively. All outcomes exceeded benchmark cutoffs. Lower ECOG status was positively correlated with longer survival (ECOG-0: 32 months, ECOG-1: 24 months, ECOG-2: 12 months, p = 0.02). Conclusion This series of portomesenteric resection in borderline resectable or locally advanced PC demonstrated a median survival of 2 years, extending to 32 months in patients with good performance status, which meet or exceed current outcome benchmarks.